The determinants of job satisfaction and auditors' performance in the Saudi context - Tahani Ali Hakami (Journal of Money and Business, 2024)
Purpose – This study aims to examine the relationship between internal and external factors and job satisfaction, and between job satisfaction and auditors’ performance. Design/methodology/approach – This research used deductive approach. Data was gathered from 83 auditors in the Saudi Organisation for Certified Public Accountants (SOCPA) database. By implementing the partial least squares-structural equation modelling (PLS-SEM) technique, the suggested hypotheses were examined. Findings – The results show that internal factors, i.e., achievement, advancement, recognition and growth, significantly impact job satisfaction. Subsequently, the external factors, i.e., company policies, relationship with a peer and relationship with supervisor, significantly impact job satisfaction. In contrast, work security has no relationship with job satisfaction. Furthermore, job satisfaction is a significant driver for auditors' performance. Research limitations/implications – This research sheds light on the relationships between internal and external factors, job satisfaction and auditors' performance in the Saudi context. It would be interesting to investigate these relationships in a different setting, such as a different country, time or industry. Future studies should broaden the sample frame to include different types of employees to obtain more generalisable results. Practical implications – This study may help managers of auditing departments formulate appropriate strategies and design effective programs to increase the level of job satisfaction between auditors by enhancing such factors, which will lead to improving the auditors' performance. Originality/value – This research provide an empirical evidence to support the theoretical assumptions of Herzberg's which is much needed.